Implementasi Penggunaan Pwntools Guna Mempermudah Eksploitasi Buffer pada Ubuntu 32-Bit - Rayhan Ramdhany Hanaputra; Nurfarida Sekar Andzani; Madany Awang Bintara; Aqwam Rosadi Kardian (Departement of Mathematics Education, 2023)
An application is a computer program that is created to work on and carry out specific tasks from the user in which the application process requires memory to run. Memory usage in an application can be used as a vulnerability that can be exploited by attackers, one of which is buffer overflow. The problem that is often encountered when exploiting a buffer overflow vulnerability is finding out where the address of the buffer is and the exploitation process usually takes a long time. There are tools that can be used to help exploit buffer overflows, namely pwntools. In this research, buffer exploitation will be carried out using automation tools to prove the ease of carrying out this attack so that it can increase awareness for developers in improving security in the programs they make. The results of this study are that using pwntools can make it easier for attackers to carry out buffer overflow attacks